The contribution of fintech (crowdfunding) to sosio-economic development in Indonesia - Rahman, Maya Puspa (2016)
With over 1.6 billion Muslims across the world, the "Halal" market is worth an estimated US$2.1 trillion a year and is growing at US$500 billion annually due to an ever-increasing Muslim population. Indonesia, having the largest Muslim population in the world, have been concentrating on the development of microfinance services, targeting to develop the microenterprises that have limited access to financial services. In line with the development of financial technology (Fintech), concerted efforts have been placed towards the socio-economic development of the low-earning families in Indonesia. One of the successful Fintech contributions is on the development of affordable houses in Jakarta through crowdfunding, which is expected to bring significant changes to the landscape of finance and growth nexus and hence towards the socio-economic development in Indonesia. As such, this paper analyzes the importance of Fintech through crowdfunding mechanism by developing an integrated database consists of all projects that have used crowdfunding platforms to raise funds. An extended analysis by employing the logistic regression is undertaken to assess on the importance of certain factors over the success rate of raising funds through this mechanism. This research documents the growing importance of crowdfunding not only to the Indonesian people, but also acts as a new gateway for entrepreneurs and investors around the world to be part of the economic development in Indonesia.